In-Vitro Antioxidant Activity of Eggplant (Epicarp Solanum Melongena L) Skin Extract on Aflatoxin-B1-Induced Rats - Chintya Darma, Gladys; Ginting, Chrismis Novalinda; Chiuman, Linda; Yuliansyah, Jeri; Hasya, Muhammad Nawal (The Islamic Education and Multiculturalism Foundation, 2025)
Eggplant skin is the outer part of the eggplant fruit (Solanum Melongena L) which has therapeutic activities such as anti-inflammatory, anti-oxidant, anti-viral, anti-bacterial and anti-cancer. This study aims to evaluate the antioxidant potential of ethanol extract of eggplant skin through phytochemical analysis, antioxidant activity through ABTS and DPPH examination by assessing IC50, and its effect on oxidative stress-related enzymes in aflatoxin B1 (AFB1)-induced rats such as MDA, LPO-4HNE, and evaluating SOD levels in rat serum. The results showed that ethanol extract of eggplant peel has significant antioxidant activity in radical scavenging activity. The antioxidant activity of ethanol extract of eggplant skin in ABTS and DPPH methods showed IC50 values with strong antioxidant potential. In the In-Vivo test, aubergine skin ethanol extract showed a good protective effect against oxidative stress with decreased MDA and LPO-4HNE levels, and increased SOD activity in AFB1-induced rats. The optimal dose of aubergine skin ethanol extract in this study is the treatment with a dose of 600mg/kgBB, which gives the best results in reducing MDA and LPO-4HNE levels, and increasing SOD activity close to the neutral group.